Foreign experience of training managers of education (Journal of Educational Sciences, 2018)
The article deals with foreign experience in training managers, knowledge and ability to manage, aswell as the system of training and selection of candidates from the staff, especially the material base, akind of features of the educational system for training managers in world practice. Along with the responsibility for all decisions made by the Manager, he must have information about the internal and external conditions of production, especially the implementation of the tasks and goals, if necessary, taking into account changes in society. In recent years, abroad, where, along with increasing competition in thetraining of managers between specialized organizations and universities, we are talking about areas oftraining and retraining in universities and business schools.The practical possibility to get practical opportunities of management and training of managers andto receive desirable result in the future is considered, in the long term there was an opportunity to comparethe best experiences of the developed countries.Much attention is paid to the study and cooperation with working groups, pay special attention tothe development of the potential of higher education institutions and the knowledge of individual students,aimed at improving the knowledge of students in the training of education managers and studiedworld experience.Key words: management, manager, education manager.